SISTEM INFORMASI PEMBAYARAN SPP SMS GATEWAY MENGGUNAKAN METODE PROTOTYPE(STUDI KASUS: SMA NEGERI 09 PALEMBANG) - Suci Nova Ramadhani; Tata Sutabri (CV. ADIBA AISHA AMIRA, 2023)
Short message service (SMS) as one of the most popular and most popular cellular services today because of its relatively easy use and very low cost. With the applications of the SMS facility for data access applications, this SMS facility can be used to access education information data for a tertiary institution. In the current technological era, it is necessary to innovate the use of technology in the world of education to assist the administration of school finances so that the data collection and processing of payment information runs effectively and efficiently. The payment system for the SPP payment system at SMA Negeri 09 Palembang is still done manually, where Administrative Officers still use books to record SPP payment data. This causes SPP data storage to still be in the form of archives, where data storage media like this are easy to damage or lose, and archives that accumulate make the performance of school employees not good. manage payment transaction data and provide information to student guardians regarding SPP transactions. SMS gateway is a system that can send two-way messages through cellular networks. The methodology used in making this application is the prototype method. With the SPP SMS Gateway payment information system application using the prototype method, it is hoped that it will make it easier to manage transactions and provide information to student guardians.